Peningkatan Kemampuan Guru PAI dalam Update Data Emis Oline Melalui BIMTEK Pada MGMP SMK Kabupaten Lombok Barat - Sukman _Sukman (Universitas Islam Negeri (UIN) Mataram, 2020)
This research aims to find out and provide understanding to PAI Teachers in updating online EMIS data. This research uses the method and design of school action carried out with a research procedure based on the Kemmis and Taggart principles. These four activities take place repeatedly in the form of cycles. From the results of the research that has been done, it can be concluded that the ability of PAI teachers in updating data needs to be improved. Therefore, efforts were made to provide understanding through technical guidance. BIMTEK which is carried out by the group and individual techniques for Islamic Education Teachers in West Lombok Regency is proven to be able to improve the ability of teachers to fill in and update online EMIS. This is evidenced by an increase in the assessment of BIMTEK instruments for each teacher.